BAHASA, TUBUH, DAN PARADIGMA PATRIARKI DALAM HUMOR KONTEMPORER INDONESIA - Hermawan, Ferry Fauzi; Waskita, Dana; Sulistyaningtyas, Tri (Jurnal Pendidikan Bahasa dan Sastra, 2017)
This study aims to analyze the construction of women in Indonesia humors that appear through the application of whatsapp conversation. This analysis is based on the opinion of Crawford (2003) and Sen (2012) about gender relations, linguistics, and humors. The focus of the study is the use of indeksial meaning and polysemy in constructing a humorous story in women. After the analysis, it was found that humors developing in the application media of whatsapp conversation tended to perpetuate sexist patriarchal values such as portraying women as a highly compliant and passive. In terms of the structure, most of the humors used several techniques of misalignment to cause the value of humor in the reader's mind. Most of the female figures appeared to be in the private or domestic space. In addition, the data show that most of the humors used figurative polysemy, especially in describing sexual activities. In this case, the women were always associated with inanimate objects, such as in describing sexual activities or woman genitals. The indeksial meanings of the language used were always based on the paradigm and the interests of men that are in line with patriarchal values. This eventually led to symbolic violence on women.Keywords: humors, polysemy, symbolic violence, women